1997
DOI: 10.3109/00016349709034902
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and magnetic resonance imaging of fetal sacrococcygeal teratoma

Abstract: Antepartal MRI is useful for examination of fetal SCT, but reliable differentiation of mature and immature SCT is not possible antepartally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…magnetic resonance imaging (MRI), have been described and several studies have been performed to define the prognostic value of these techniques. Kirkinen et al [26] noted that prenatal MRI was helpful in the accurate definition of the intrapelvic extension of the SCT. The assessment of the extrapelvic tumor, including vascularity and differentiation of the tumor type was, however, not aided by this imaging modality.…”
Section: Diagnosismentioning
confidence: 99%
“…magnetic resonance imaging (MRI), have been described and several studies have been performed to define the prognostic value of these techniques. Kirkinen et al [26] noted that prenatal MRI was helpful in the accurate definition of the intrapelvic extension of the SCT. The assessment of the extrapelvic tumor, including vascularity and differentiation of the tumor type was, however, not aided by this imaging modality.…”
Section: Diagnosismentioning
confidence: 99%
“…This information is important, since it will affect the postnatal surgical approach to the lesion (101). Fetal MR imaging has been shown to be useful for planning postpartum surgery (86,97,99,101), and for decision-making regarding the timing and mode of delivery (101).…”
Section: Non-cns Anomaliesmentioning
confidence: 99%
“…It is important to note that although the pelvic extension of the tumor was sonographically detected before surgery, it was grossly underestimated. Kirkinen et al [14] reported that ultrasound examination alone, unlike MRI, was not able to reliably discern the intrapelvic extent of an SCT due to acoustic shadowing by the fetal pelvic bones. Fast spin MRI may be helpful for more accurate preoperative assessment since it enables sufficient outlining of the intrapelvic structures without fetal movement artifacts.…”
Section: Discussionmentioning
confidence: 99%